Effect of Some Botanicals against Termites, Macroterms Spp. (Isoptera: Termitidae) Under Laboratory Conditions - Shiberu, Tadele; Ashagere, Habtamu; Negeri, Mulugeta (International Journal of Sustainable Agricultural Research, 2014)
Seven different plant extracts as botanical insecticides were evaluated for their toxicity against termites in Ethiopia. Aqueous extracts of tobacco leaves (Nicotianatabacum), Birbira seeds (Militia ferruginea) and Endod leaves (Phytolaccadodecandra) were achieved 100% mortality after 24 hours which as did positive control (chloropyrifos 48% E.C). Also Pyrethrum E-185 flowers (Chrysanthemum sp.) caused an average of 91.25% mortality in both workers and soldiers termites with no significant difference between them. Neem seeds (Azadirachtaindica), Kosso seeds (Hageniaabyssinica) and Bisana seeds (Croton macrostachys) were less active than the other botanicals but significantly better than the negative control. Bisana seeds (Croton macrostachys) was less toxic effect among all treatments even after 5 days. All treatments were more effective against workers termites than against soldiers termites.